Betalain-rich concentrate supplementation improves exercise performance in competitive runners - Van Hoorebeke, J. S.; Trias, C. O.; Davis, B. A.; Lozada, C. F.; Casazza, G. A. (Sports, 2016)
This study aimed to determine the effects of a betalain-rich concentrate (BRC) of red beets, containing antioxidant and anti-inflammatory properties, on performance and exercise-related muscle damage. Thirteen (25.3 ± 5.4 years) competitive male runners completed two double-blind, cross-over, randomized trials (BRC and control) separated by seven days. Each trial was preceded by six days of supplementation with 100 mg of BRC or control. On the seventh day, exercise trials commenced 150 min after supplementation with 50 mg BRC or control and consisted of 30 min of treadmill running (77 ± 4% VO2max) followed by a 5-km time trial (TT). During exercise at the same intensity, BRC resulted in a 3% lower heart rate, a 15% lower rate of perceived exertion (RPE) and a 14% lower blood lactate concentration compared to the control (p = 0.05). Five-kilometer TT duration (23.0 ± 4.2 versus 23.6 ± 4.0 min) was faster in 10 of the 13 subjects, and RPE was lower (p < 0.05) with the BRC treatment compared to the control. Lactate dehydrogenase, a marker of muscle damage, increased less from baseline to immediately and 30 min after the 5-km TT with the BRC treatment, despite no differences in subjective measures of muscle soreness and fatigue. In summary, BRC supplementation improved 5-km performance time in male competitive runners